The importance of the microbiome in pediatrics and pediatric infectious diseases. Issue 1 (February 2018) - Gaufin, Thaidra; Tobin, Nicole H.; Aldrovandi, Grace M.
Abstract : Purpose of review: Emerging research on the pediatric microbiome implicates the importance of the microbiome on the development of the immune system, nervous system, and growth. Changes to the microbiome during infancy are associated with the development of chronic illnesses such as asthma and inflammatory bowel disease. Additionally, the microbiome provides protection against certain pathogens, affects vaccine responses, and alters drug metabolism. This review highlights what is known about the microbiome, the establishment of a healthy microbiome and the significance that changes to the microbiome composition have on growth and health of children and adolescents. Recent findings: Vaginal delivery, breastfeeding, maternal health, and nutrition help shape a healthy microbiome. Caesarian delivery, formula feeding, and antibiotic use perturb the microbiome and are associated with the development of type II diabetes, asthma, allergic diseases, and obesity later in life. Specific interventions using pre and probiotics in multiple settings are under investigation with limited success. Summary: A better understanding of the microbiome and the interaction with the immune system may help guide interventions to alter the microbiome toward a state of lifelong health.